2023
DOI: 10.1111/iju.15187
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lower urinary tract symptoms and frailty

Abstract: Objective To elucidate the relationship between frailty and lower urinary tract symptoms (LUTS). Methods We longitudinally evaluated the temporal changes and the relationships between frailty and LUTS in 247 community‐dwelling adults (45 years or older) at baseline and at a 5‐year follow‐up. We used the Fried phenotype (phenotype‐based frailty), 5‐item modified frailty index (5i‐mFI; comorbidity‐based frailty), and frailty discriminant score (comprehensive frailty assessment) to evaluate frailty. LUTS were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, one publication found that nocturia is associated with low hip abductor strength [ 49 ], linking bladder function and muscle strength or sarcopenia, respectively. As to comorbidity, a high comorbidity burden and vascular risk factors predicted more severe or prevalent LUTS [ 43 , 50 ], while exercise was shown to decrease LUTS [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, one publication found that nocturia is associated with low hip abductor strength [ 49 ], linking bladder function and muscle strength or sarcopenia, respectively. As to comorbidity, a high comorbidity burden and vascular risk factors predicted more severe or prevalent LUTS [ 43 , 50 ], while exercise was shown to decrease LUTS [ 51 ].…”
Section: Resultsmentioning
confidence: 99%